1986
DOI: 10.1145/1013812.18186
|View full text |Cite
|
Sign up to set email alerts
|

A framed movable-boundry protocol for integrated voice/data in a LAN

Abstract: A new, fully-distributed protocol for integrated voice/data traffic in a local-area, random-access broadcast network is described. The protocol introduces a movable voice-data boundary to framed TDMA/CSMA and eliminates the requirement of system-wide synchronized clocks. The movable boundary is a major advantage in any system where fluctuations in voice and data loads are expected because assignment of idle capacity from one traffic class to the other increases the utilization of the channel. The protocol prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the past, extensive analysis and simulation have demonstrated the feasibility and performance capability of DRAMA [4][5][6][7][8]. As a first step to be assured that H3M can be provide similar performance in an extended environment, it is necessary to extend the analysis of DRAMA into the areas where differences occur.…”
Section: Performance Of H3mmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, extensive analysis and simulation have demonstrated the feasibility and performance capability of DRAMA [4][5][6][7][8]. As a first step to be assured that H3M can be provide similar performance in an extended environment, it is necessary to extend the analysis of DRAMA into the areas where differences occur.…”
Section: Performance Of H3mmentioning
confidence: 99%
“…Considerable analytical and simulation work was conducted to document the CSMAlCD performance for DRAMA [4][5]. The early work [4] plus work by others [9,25] examined the effect of framing on CSMAlCD while the later work [5] showed that when a LAN uses multiple channels, it is more effective to segregate the synchronous and asynchronous data onto separate channels. WM does not have this option available, so we needed to extend the original work to verify that changing bandwidth and sending frequencies is a feasible alternative method for load balancing.…”
Section: Performance Of H3mmentioning
confidence: 99%
“…This protocol introduces a movable voice-data boundary to framed TDMA/CSMA and eliminates the requirement of system wide synchronized clocks [50]. The movable boundary is a major advantage in any system where fluctuations in voice and data loads are expected because assignment of the idle capacity from one class to the other increases the utilization of the channel.…”
Section: Movable Boundary Protocol For Integrated Voice/datamentioning
confidence: 99%
“…• CSMA/CD may be used for voice transmission, provided the basic CSMA/CD operation is altered [50,38]. This approach may either be expensive or infea-sible.…”
Section: Csma/cd Is Ruled Out: Why ?mentioning
confidence: 99%
See 1 more Smart Citation